An in-depth understanding of stakeholders’ experiences about their participation in the co-production of ‘Maze Out’: a serious game for the treatment of eating disorders - Maria Mercedes Guala; Aida Bikic; Kim Bul; David Clinton; Anette Søgaard Nielsen; Helene Nygaard Nielsen; Martina Scarpelli; Luciana Schneider; Regina Christiansen (Journal of Eating Disorders)
Abstract Background Co-production is increasingly used in mental health research and clinical settings. Maze Out is a digital game co-produced by clinicians, patients with eating disorders (EDs), an art director with lived experience in EDs, and a game-developing company. Maze Out is based on everyday challenges when suffering from EDs and is currently being evaluated as a supplement tool in EDs treatment. Several studies on co-producing mental health interventions focus on design and effectiveness, but the experiences of those involved in the co-production process remain unexplored. An in-depth exploration of stakeholders’ experiences offers valuable insights into the impact of co-production on different groups and generates crucial knowledge for successful implementation. Objectives This study evaluated and explored the co-production process and the meaning that EDs patients, clinicians, and game designers attributed to their participation in the co-production of Maze Out. The objectives were to determine (1) how stakeholders experienced their collaboration in the co-production of Maze Out.; and (2) to what extent the stakeholders involved in developing Maze Out followed Cahn’s principles of equality, diversity, accessibility, and reciprocity. Methods Five stakeholders (two patients, two clinicians, and a game designer) who participated in the co-production completed semi-structured interviews. Two patients and one clinician’s diaries supplemented the interviews. Reflexive thematic analysis was used to interpret the data. Results The results of this study highlight the importance of building a common language between clinicians, patients, and other professionals involved in developing new forms of treatment and interventions. A recommendation for researchers and clinicians to implement co-production in the future is that Cahn’s principles: equality, reciprocity, accessibility, and diversity, serve as a strong foundation for successful co-production. In this study, three and partially one of the four Cahn’s principles about co-production were identified: equality, reciprocity, and accessibility. When applied in an ED context, these principles provided stakeholders with valuable insights, enriching practice-based knowledge, using the knowledge applicable to clinical practice, and demonstrating their crucial role in fostering effective co-production processes.